Congenital Heart Disease in Pediatric and Adult Patients : Anesthetic and Perioperative Management - Dabbagh, Ali; Conte, Antonio Hernandez; Lubin, Lorraine (Springer International Publishing : Imprint: Springer, 2017)
Congenital Heart Disease in Pediatric and Adult Patients: Anesthetic and Perioperative Management provides a comprehensive, up-to-date overview of care of the pediatric patient undergoing cardiac surgery and anesthesia. After introductory chapters that encompass pediatric cardiovascular embryology, physiology and pharmacology, diagnostic approaches and preoperative considerations are explained. The intraoperative management of a wide range of specific lesions is then discussed, with full descriptions of anesthesia plans added with descriptions on diagnostic methods and surgical interventions. Postoperative care is also addressed, and a concluding section considers anesthesia outside the cardiac operating room. In the twenty-first century, advances in minimally invasive technology have led to the introduction of a wide array of pediatric cardiac procedures. More traditional surgical procedures have also been transformed by new devices and surgical approaches. The cardiac anesthesiologist is faced with an ever-increasing role in the perioperative care of pediatric patients undergoing cardiologic procedures in operating rooms, as well as less conventional locations. In this book, accomplished experts from around the world in the fields of pediatric anesthesia, cardiology, and cardiac surgery describe the multiple facets of caring for this very unique patient population.